The association between symptoms of developmental coordination disorder and neuropsychological characteristics in children with and without ADHD - Lee, Taeyeop; Lim, Jongseok; Kim, Seonok; Kim, Jichul; Park, Kee Jeong; Joung, Yoo-Sook; Kim, Hyo-Won (Frontiers in Psychiatry, 2024)
Objective: Attention-deficit/hyperactivity disorder (ADHD) frequently co-occurs with developmental coordination disorder (DCD). This study aimed to evaluate the association between DCD symptoms and neuropsychological characteristics in children with and without ADHD.We recruited 298 children aged 5-12 years. Motor performance was assessed using the Developmental Coordination Disorder Questionnaire (DCDQ), while ADHD symptoms were assessed using the ADHD Rating Scale (ARS) and the Advanced Test of Attention (ATA). Cognitive characteristics were measured using the Wechsler Intelligence Scale, and behavioral characteristics were assessed using the Korean Personality Rating Scale for Children.The children had a mean age of 7.6 ± 1.7 years, with 214 (71.8%) being boys. Among children diagnosed with ADHD (n = 176), 39.2% exceeded the DCDQ cutoff score, compared to 4.1% in the neurotypical group (n = 122). In the correlation analysis, the DCDQ total score was significantly correlated with ARS, omission and commission errors in visual and auditory ATA, and full-scale intellectual quotient. In addition, symptoms of depression, social dysfunction, and psychosis were correlated with the DCDQ total score.In the between-group analysis, children with both ADHD and DCD exhibited more omission errors on the auditory ATA and behavioral problems related to depression, social dysfunction, and psychosis compared to children with ADHD only.Our study indicates that children with ADHD exhibit more difficulties in motor performance.Children with both ADHD and DCD may present with a greater burden of psychiatric conditions than children with ADHD only, suggesting the need for careful monitoring in clinical practice.